Naturalistic study on the use of clozapine in the early phases of non-affective psychosis: A 10-year follow-up study in the PAFIP-10 cohort. (September 2022) - Moreno-Sancho, Lara; Juncal-Ruiz, Maria; Vázquez-Bourgon, Javier; Ortiz-Garcia de la Foz, Victor; Mayoral-van Son, Jacqueline; Tordesillas-Gutierrez, Diana; Setien-Suero, Esther; Ayesa-Arriola, Rosa; Crespo-Facorro, Benedicto
Abstract: Clozapine is seldom prescribed in treatment-resistant schizophrenia (TRS) patients during early phases of the illness. We aimed to examine the pathway and patterns and the impact of clozapine use in patients with TRS who were followed up for 10 years after the first outbreak of the illness. Data were obtained retrospectively from an epidemiological cohort of first episode schizophrenia patients (n = 218) who had been treated in a specialized intervention program (PAFIP). Out of 218, 35 (16%) individuals were on clozapine at 10-year assessment, while 183 (84%) were taking other antipsychotics. Among those 183 psychosis subjects who were not on clozapine, 13 (7.1%) met criteria for TRS. In the clozapine group, ten (28.6%) met criteria for early-TR and twenty-five (71.4%) met criteria for late-TR. Before clozapine treatment was initiated, the median number of days under other antipsychotic treatment was 1551 days (IQR = 1715) and the median time that subjects remained on clozapine was 6.3 years (IC95%: 5.49–7.20). At 10 years, we found that those individuals taking clozapine had higher CGI total scores (F = 12.0, p = 0.001) and SANS total scores (F = 9.27, p = 0.003) than subjects taking other antipsychotics after correcting for baseline values. Interestingly, when performing these analyses at 10 years between subjects taking clozapine (n = 35) and subjects who despite meeting TRS criteria were not taking clozapine (n = 13), we found that subjects taking clozapine had significantly lower total scores on all clinical scales compared with subjects who met TRS criteria and were not taking clozapine (p values < 0.05). TRS patients who took the longest time to start clozapine (third tertile) showed significantly higher CGI scores at 10-year follow-up compared to those who initiated clozapine earlier (first tertile) (t = 2.60; p = 0.043). Our findings reinforce the need of a timely assessment of treatment-resistant criteria in early schizophrenia patients and highlight the long-term benefits of an early introduction of clozapine on those patients meeting treatment-resistant criteria.